A2.2 Kidneys declined for paediatric transplantation have good short-term renal allograft survival if eventually transplanted. (4th October 2017) - Marlais, M; Pankhurst, L; Bradbury, L; Tizard, EJ; Marks, SD
Abstract : Background: Kidneys offered for paediatric transplantation may be declined for a variety of donor or recipient specific factors. The aims of this study were to determine the outcome of kidneys declined for paediatric recipients and establish renal allograft survival in kidneys that were eventually transplanted. Methods: Data from NHS Blood and Transplant were collected for all kidneys offered and declined for paediatric recipients under 18 years of age from 2009 to 2014. The eventual outcome of declined kidneys was recorded, as well as three-year renal allograft survival in those kidneys that were eventually transplanted. The outcome for children who had a kidney declined on their behalf was also analysed. Results: 615 kidneys were available for transplantation from donors initially declined for kidney transplantation to 204 different paediatric recipients. 82% of the 615 declined kidneys were eventually transplanted, 7% of kidneys went to paediatric recipients and 62% of kidneys went to adult recipients. Three year renal allograft survival in the kidneys that went to paediatric recipients was 82% (95% CI 67%–91%). 84% of the 204 children who initially had an offer declined on their behalf were eventually transplanted and have a functioning graft, 11% of children are still waiting for a kidney transplant. The waiting time for a child to be transplanted with a DBD kidney after an offer was declined for them was 0 to 1701 (median 198) days. Conclusion: This study reports good short-term renal allograft survival in kidneys that were initially declined for paediatric recipients and then subsequently transplanted. While most children who have a kidney declined on their behalf will eventually be transplanted, they wait more than 6 months on average to get a kidney transplant. In view of the advantages of timely transplantation in children, criteria for accepting kidneys for paediatric recipients could be reviewed.